2015
DOI: 10.1002/cld.431
|View full text |Cite
|
Sign up to set email alerts
|

Single‐incision laparoscopic cholecystectomy

Abstract: Watch a video presentation of this article Answer questions and earn CME

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Minimally invasive surgery is one of the growing developments of surgery. At present, single-incision endoscopic surgeries such as single-incision appendectomy and single-incision cholecystectomy are widely performed [55,56]. Since Gonzalez's rst report of single-incision VATS lobectomy [57], retrospective studies have shown that single-incision VATS lobectomy is safe and feasible [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery is one of the growing developments of surgery. At present, single-incision endoscopic surgeries such as single-incision appendectomy and single-incision cholecystectomy are widely performed [55,56]. Since Gonzalez's rst report of single-incision VATS lobectomy [57], retrospective studies have shown that single-incision VATS lobectomy is safe and feasible [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Now, a new and even less invasive technique is emerging in an attempt to further improve outcomes for patients undergoing removal of the gallbladder. Robotic single-site cholecystectomy (RSSC) is rapidly emerging as a safe and feasible alternative to conventional 4-port laparoscopic techniques [3][4][5]. Current research suggests significant benefits of a single-incision for operative use including improved cosmetics and shorter hospital stays [6], but more research is needed to investigate the efficacy of RSSC and which patient populations are most suited for this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…With enhanced experience and more advanced instrumentation, new less invasive approaches are preferred to further reduce post-operative pain, improve cosmesis and decrease recovery time in minimally invasive surgery (Bisgaard et al 2002;Chang et al 2020;Shaikh et al 2017). New techniques such as natural ori ce translumenal endoscopic surgery (NOTES) (Auyang et al 2009;Gumbs et al 2009) and single-incision laparoscopic surgery (SILS) (Castellanos et al 2015;Yamazaki et al 2015)have been developed in the eld of cholecystectom. However, NOTES technique is still controversial as it requires a long and di cult operation process and a multidisciplinary team.…”
Section: Introductionmentioning
confidence: 99%